Pengaruh Atraksi, Amenitas, Dan Aksesibilitas Terhadap Kunjungan Ulang Wisatawan Lokal : Studi Di 4 Destinasi Wisata Kabupaten Penajam Paser Utara - Heni Nurhayati; St. Rukaiyah; Nurmadhani Fitri Suyuthi (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
This research focuses on four tourist destinations in North Penajam Paser Regency: Istana Amal Beach, Nipah-Nipah Beach, Tanjung Jumlai Beach, and D’Wish Gunung Mulia. Attractions, amenities, and accessibility are considered key factors influencing repeat visits. Based on data analysis, attractions, especially natural beauty and environmental cleanliness, have a significant influence on repeat visits by tourists. Thus, the hypothesis stating a positive influence between Attractions and repeat visits by tourists to the four tourist destinations in North Penajam Paser Regency is partially accepted. However, amenities such as accommodation and dining places do not significantly affect repeat visits. Therefore, the hypothesis stating a positive influence between amenities and repeat visits by tourists to the four tourist destinations in North Penajam Paser Regency is partially rejected. On the other hand, accessibility such as ease of road access and clear signage has a positive influence on repeat visits. Thus, the hypothesis stating a positive influence between Accessibility and repeat visits by tourists to the four tourist destinations in North Penajam Paser Regency is partially accepted.Overall, Attractions, Amenities, and Accessibility collectively influence tourist repeat visits. This indicates that the management and development of tourist destinations need to consider these factors. Although Amenities have less significant influence, it is important to continue improving and enhancing supporting facilities at tourist destinations. The findings of this research provide valuable insights for tourism managers and policymakers to improve the quality and attractiveness of destinations and strengthen the position of North Penajam Paser Regency as an appealing tourist destination for local tourists.